Structure of somatic pathology in patients with rhonchopathy - M. A. Ryabova; S. A. Karpishchenko; M. Yu. Ulupov; A. R. Faizova; A. V. Zinchenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Snoring is a sound phenomenon that is often a symptom of more serious condition – OSAS (obstructive sleep apnea syndrome). All patients with complaints of nocturnal snoring, daytime sleepiness, breathing stops in sleep, in addition to the standard otorhinolaryngological examination at the initial consultation should be diagnosed using validated questionnaires, scales to determine the presence of risk of OSAS, according to the results of which a decision is made to consult a -somnologist with further additional examination.The objective of this work was to evaluate the clinical manifestations, concomitant pathology, and complications in patients at the initial visit to an otorhinolaryngologist complaining of the presence of the acoustic phenomenon of snoring.Methods and materials. 304 patients with the diagnosis of rhonchopathy were examined. The inclusion criterion was the presence of the acoustic phenomenon of snoring. All patients underwent computed tomography of the maxillofacial region using contrast technique of the soft palate before radiation diagnosis with the followed morphometry.Results. Analyzing the results of our sample, we come to a clear understanding that each case is very individual and needs a balanced interdisciplinary approach.Conclusions. When choosing the treatment method for rhonchopathy, it is necessary to take into account the patient’s somatic status, BMI, the presence of chronic tonsillitis and other concomitant diseases to choose the volume and method of surgical treatment